TFPI-2 Protects Against Gram-Negative Bacterial Infection - Ali, Mohamad N.; Kasetty, Gopinath; Elvén, Malin; Alyafei, Saud; Jovic, Sandra; Egesten, Arne; Herwald, Heiko; Schmidtchen, Artur; Papareddy, Praveen (Frontiers in Immunology, 2018)
Tissue factor pathway inhibitor-2 (TFPI-2) has previously been characterized as an endogenous anticoagulant. TFPI-2 is expressed in the vast majority of cells, mainly secreted into the extracellular matrix. Recently we reported that EDC34, a C-terminal peptide derived from TFPI-2, exerts a broad antimicrobial activity. In the present study, we describe a previously unknown antimicrobial mode of action for the human TFPI-2 C-terminal peptide EDC34, mediated via binding to immunoglobulins of the classes IgG, IgA, IgE, and IgM. In particular the interaction of EDC34 with the Fc part of IgG is of importance since this boosts interaction between the immunoglobulin and complement factor C1q. Moreover, we find that the binding increases the C1q engagement of the antigen-antibody interaction, leading to enhanced activation of the classical complement pathway during bacterial infection. In experimental murine models of infection and endotoxin challenge, we show that TFPI-2 is up-regulated in several organs, including the lung. Correspondingly, TFPI-2-/- mice are more susceptible to pulmonary P. aeruginosa bacterial infection. No anti-coagulant role of TFPI-2 was observed in these models in vivo. Furthermore, in vivo, the mouse TFPI-2-derived C-terminal peptide VKG24, a homolog to human EDC34 is protective against systemic E. coli bacterial infection. Moreover, in sputum from cystic fibrosis patients TFPI-2 C-terminal fragments are generated and found associated with immunoglobulins. Together our data describe a previously unknown host defense mechanism and therapeutic importance of TFPI-2 against invading Gram-negative bacterial pathogens.